PENYULUHAN PENCEGAHAN PENYAKIT HIPERTENSI DI DESA SALIMULI KECAMATAN GALELA UTARA - Cabu, Roberto; Christin Fika, Elfira (HIRONO : Jurnal Pengabdian Masyarakat, 2023)
The purpose of conducting counseling in Salimuli Village is to increase knowledge about hypertension, classification, causes and ways of prevention and control. The activity, which was attended by 25 participants of Salimuli Village, was carried out in collaboration with the Public Health Study Program of Hein Namotemo University with the Salimuli Village government, along with the implementation of Field Learning Practices (PKL) students in this village.  The results of the evaluation of the implementation of activities show that there is an increase in public knowledge, especially related to knowledge of the causes of hypertension, types of hypertension, as well as ways to prevent and overcome hypertension.